The Problem of Violence in Student Groups - Eniņa – Briede, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The problem of violence student's collective concern to the community. Violence is out of control and almost every day we learn some new events that are painful for both children and their parents. In his article I was looking for opportunities to use art to solve the problem acute. As an artist myself and cultural history teacher I find this theme is very close and I am sure that every artistic genre emotionally beneficial effect on a child's character. Artistic impression of the child becomes positive, emotionally open is just to find the right approach for each individual child.